Establishing a population-based patient-reported outcomes study (PROMs) using national cancer registries across two jurisdictions: the Prostate Cancer Treatment, your experience (PiCTure) study. Issue 4 (17th April 2015) - Drummond, F J; Kinnear, H; Donnelly, C; O'Leary, E; O'Brien, K; Burns, R M; Gavin, A; Sharp, L
Abstract : Objective: To establish an international patient-reported outcomes (PROMs) study among prostate cancer survivors, up to 18 years postdiagnosis, in two countries with different healthcare systems and ethical frameworks. Design: A cross-sectional, postal survey of prostate cancer survivors sampled and recruited via two population-based cancer registries. Healthcare professionals (HCPs) evaluated patients for eligibility to participate. Questionnaires contained validated instruments to assess health-related quality of life and psychological well-being, including QLQ-C30, QLQ-PR25, EQ-5D-5L, 21-question Depression, Anxiety and Stress Scale (DASS-21) and the Decisional Regret Scale. Setting: Republic of Ireland (RoI) and Northern Ireland (NI). Primary outcome measures: Registration completeness, predictors of eligibility and response, data missingness, unweighted and weighted PROMs. Results: Prostate cancer registration was 80% (95% CI 75% to 84%) and 91% (95% CI 89% to 93%) complete 2 years postdiagnosis in NI and RoI, respectively. Of 12 322 survivors sampled from registries, 53% (n=6559) were classified as eligible following HCP screening. In the multivariate analysis, significant predictors of eligibility were: being ≤59 years of age at diagnosis (p<0.001), short-term survivor (<5 years postdiagnosis; p<0.001) and from RoI (p<0.001). 3348 completed the questionnaire, yielding a 54% adjusted response rate. 13% of men or their families called the study freephone with queries for assistance with questionnaire completion or to talk about their experience. Significant predictors of response in multivariate analysis were: being ≤59 years at diagnosis (p<0.001) and from RoI (p=0.016). Mean number of missing questions in validated instruments ranged from 0.12 (SD 0.71; EQ-5D-5L) to 3.72 (SD 6.30; QLQ-PR25). Weighted and unweighted mean EQ-5D-5L, QLQ-C30 and QLQ-PR25 scores were similar, as were the weighted and unweighted prevalences of depression, anxiety and distress. Conclusions: It was feasible to perform PROMs studies across jurisdictions, using cancer registries as sampling frames; we amassed one of the largest, international, population-based data set of prostate cancer survivors. We highlight improvements which could inform future PROMs studies, including utilising general practitioners to assess eligibility and providing a freephone service.